Cenozoic geodynamic and tectonomagmatic evolution of Andean margin, implications for metallogenic endowment of orogenic belts - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
The genesis and distribution of porphyry copper deposits have long been studied due to the pivotal role this commodity has in economic development. However, they remain poorly understood and continue to be a topic of global interest. Although porphyry formation is typically associated with convergent plate margins, these deposits and their associated magmatic arcs are not uniformly distributed along such boundaries, which calls for alternative or complementary hypotheses to explain these differences. In this contribution, we explore the processes that play a role in the metal endowment of the continental crust, focusing on the heterogeneity of the subducting and overriding plates during the Cenozoic in the Central Andes. By reconstructing the tectonic interactions of oceanic and continental plates and analyzing a large set of 2355 igneous rock compositions (1770 pre-Quaternary), we examine these dynamics along the Andean margin, from northern Peru to central Chile. A significant finding is the pronounced spatio-temporal relationship between the subduction of hotspot tracks (from Easter, San Felix and Juan Fernandez hotspots) and the genesis of porphyry copper deposits in the region, which are predominantly situated south of the hotspot tracks. Additionally, the trace element composition and distance to the trench of magmatic events display a distinct contrast between the northern and southern segments of the hotspot ridge subduction along the Andes. These observations suggest that seamount chain subduction may have played a primary role in lithospheric deformation and magma composition in the Andean orogen during the Cenozoic.